The Similarities and Differences in the Localization of Buddhism and Christianity—Taking the Discussional Strategies and Intellectual Backgrounds of Tertullian’s Apology and Mou Zi’s Answers to the Skeptics as Examples - Wang, Lin (Religions, 2024)
After the rise of Christianity in the Roman Empire and the introduction of Buddhism into China, Christianity and Buddhism were both faced with the adjustment of the existing society. In the Roman Empire, faced with some censure, apologists began to write articles to clarify misunderstandings and express their beliefs. At the same time, there are similar argumentative documents on Buddhism in China. Their argumentation ideas also have many similarities, such as, firstly, distinguishing them from the original ideas, then using the existing ideas, and finally, actively integrating them into existing society. However, there are some bigger differences in the background of the debate between the Roman Empire and China—Christianity has strong political independence. The most fundamental difference is the atmosphere of the existing ruling ideology—China has been Confucianized, and the political independence of Confucianism is relatively weak. It is this fundamental difference that finally led to the final difference in the development paths of Christianity in the Roman Empire and Buddhism in China, which then affected their historical paths.